Low carbohydrate diets in eating disorders and type 1 diabetes. (July 2021) - Hart, Melissa; Pursey, Kirrilly; Smart, Carmel
Dietary intake requires attention in the treatment of both eating disorders and type 1 diabetes (T1D) to achieve optimal outcomes. Nutritional management of both conditions involves encouraging a wide variety of healthful foods in the context of usual cultural and family traditions. In recent times, low carbohydrate diets have seen a rise in popularity, both in T1D and in the general population. Low carbohydrate diets involve dietary restriction, although the extent depends on the level of carbohydrate prescription. Although dietary restriction is a known risk factor for eating disorders, there is limited literature on the impact of following a low carbohydrate diet on the development and maintenance of eating disorders in T1D. The aim of this review is to discuss the impact of dietary restriction on the development and treatment of eating disorders and propose considerations to enable optimum health outcomes in individuals with T1D, an at risk group. In order to achieve this, clarity regarding strategies that allow both flexibility in dietary intake and facilitate healthy eating behaviours, whilst achieving glycaemic targets, are required.